Single-cell transcriptome analysis reveals a cellular immune response in freshwater dark sleeper (Odontobutis potamophila) after infection with Aeromonas veronii - Liu, Guoxing; Zhu, Chenxi; Gao, Xiaojian; Zheng, You; Zhu, Xinhai; Jiang, Hucheng; Wei, Wanhong; Jiang, Qichen; Zhang, Xiaojun (Frontiers in Physiology, 2023)
The bacterium Aeromonas veronii is a co-pathogenic species that can negatively impact the health of both humans and aquatic animals. In this study, we used single-cell transcriptome analysis (scRNA-seq) to investigate the effects of infection with A. veronii on head kidney cells and the regulation of gene expression in the dark sleeper (Odontobutis potamophila). scRNA-seq was used to assess the effects of infection with A. veronii in O. potamophila B cells, endothelial cells, macrophages, and granulocytes, and differential enrichment analysis of gene expression in B cells and granulocytes was performed. The analyses revealed a significant increase in neutrophils and decrease in eosinophils in granulocytes infected with A. veronii. Activation of neutrophils enhanced ribosome biogenesis by up-regulating the expression of RPS12 and RPL12 to fight against invading pathogens. Crucial pro-inflammatory mediators IL1B, IGHV1-4, and the major histocompatibility class II genes MHC2A and MHC2DAB, which are involved in virulence processes, were upregulated, suggesting that A. veronii activates an immune response that presents antigens and activates immunoglobulin receptors in B cells. These cellular immune responses triggered by infection with A. veronii enriched the available scRNA-seq data for teleosts, and these results are important for understanding the evolution of cellular immune defense and functional differentiation of head kidney cells.